The H2A.Z and PWWP2A associated NuRD interactor HMG20A controls transcriptional programs in head and heart development - Herchenröther, Andreas; Justus Liebig University Giessen (My University, 2023)
The inheritable information of all eukaryotic organisms is organized in DNA-protein complexes called chromatin. Dedicated chromatin-binding proteins are required for DNA-based processes during development. The recently established direct histone variant H2A.Z interactor PWWP2A is involved in craniofacial development. During my PhD work, I identified the H2A.Z/PWWP2A-associated High mobility group protein 20A (HMG20A) as part of several chromatin-modifying complexes, including the nucleosome remodeling and deacetylase (NuRD) complex, and showed its localization to distinct genomic regulatory regions. Furthermore, HMG20A depletion causes severe head and heart developmental defects in Xenopus laevis. Data gathered here suggest that craniofacial malformations are caused by defects in neural crest cell (NCC) migration and cartilage formation. These developmental defects are replicated in HMG20A-depleted mouse embryonic stem cells (mESCs), which show inefficient differentiation into NCCs and cardiomyocytes (CM). Loss of HMG20A, which marks promoters and enhancers, results in chromatin accessibility changes and a striking deregulation of transcription programs involved in epithelial-mesenchymal transition (EMT) and differentiation processes. Collectively, my study implicates HMG20A as part of the H2A.Z/PWWP2A/NuRD-axis and reveal it as a key modulator of sophisticated developmental transcription programs that guide the differentiation of NCCs and CMs.
Keywords: ddc:570